Human Endothelial Cell Spheroid-based Sprouting Angiogenesis Assay in Collagen - Tetzlaff, Fabian (Bio Protoc, 2018)
Angiogenesis, the formation of new blood vessels from pre-existing ones plays an important role during organ development, regeneration and tumor progression. The spheroid-based sprouting assay is a well-established and robust method to study the influence of genetic alterations or pharmacological compounds on capillary-like tube formation of primary cultured endothelial cells. A major advantage of this assay is the possibility to study angiogenesis in a 3D environment. Endothelial cells are cultured as hanging drops to form spheroids. Those spheroids are embedded into a collagen matrix and tube formation is analyzed 24 h later. By analyzing sprout number and sprout length the effects of genetic manipulation or drug treatment on angiogenesis can be investigated.